2020
DOI: 10.1177/0033354920970179
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Mental Health Symptoms Among US Adults During COVID-19, March–April 2020

Abstract: Objectives An understanding of mental health symptoms during the coronavirus disease 2019 (COVID-19) pandemic is critical to ensure that health policies adequately address the mental health needs of people in the United States. The objective of this study was to examine mental health symptoms among US adults in an early stage of the COVID-19 pandemic. Methods We conducted a cross-sectional study in late March 2020 with a national sample of 963 US adults using an online research platform. Participants self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 20 publications
3
29
1
1
Order By: Relevance
“…Regarding cognitive outcomes, our findings do not seem to align with previous evidence (Fiorenzato et al, 2021;Reading Turchioe et al, 2021), which included self-reported measures of cognitive complaints leading to an over or underestimation of cognitive changes compared to objective outcomes implemented in this study. The well-known age-related differences in favor of younger adults (e.g., Park, 2002;Borella et al, 2007) were confirmed for both the WM measure and the word list recall tasks.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Regarding cognitive outcomes, our findings do not seem to align with previous evidence (Fiorenzato et al, 2021;Reading Turchioe et al, 2021), which included self-reported measures of cognitive complaints leading to an over or underestimation of cognitive changes compared to objective outcomes implemented in this study. The well-known age-related differences in favor of younger adults (e.g., Park, 2002;Borella et al, 2007) were confirmed for both the WM measure and the word list recall tasks.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, little attention has been devoted to understanding whether and to what extent the COVID-19 lockdown and the following restrictions have affected such other crucial domain of our functioning, as the cognitive one, however. The two studies that examined the COVID-19 lockdown influence in this domain, highlighted that attention, executive functions, and temporal orientation (Fiorenzato et al, 2021), as well as daily functioning (Reading Turchioe et al, 2021), were perceived as the most affected cognitive abilities during the lockdown, whereas an improvement in the memory domain was perceived (Fiorenzato et al, 2021). Also, younger adults reported higher cognitive complaints than their older counterpart (Fiorenzato et al, 2021;Reading Turchioe et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Closing schools has affected more than 1,300,000,000 learners worldwide (Unesco, 2020). However, members from vulnerable groups (individuals with poor financial resources, poor health literacy, or with self-reported disabilities) have faced a greater adversity in relation to mental health, especially anxiety and depression (Reading Turchioe et al, 2021), and access to education (Long et al, 2020). This is the case of individuals with intellectual disabilities, who have suffered greater consequences during the pandemic (Courtenay, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These findings were unexpected, as several reports have noted that increased anxiety and depressive symptoms have been observed during the COVID-19 outbreak compared with historical norms. [3][4][5]…”
mentioning
confidence: 99%